Fiducia in Public Law - Breach, Lindsay (Victoria University of Wellington Law Review, 2017)
Breach advances a conceptual basis for understanding fiduciary relationships in a public law setting. Fiduciary concepts cut across traditional legal boundaries to encompass a broad array of legal relationships. Political theorists and legal commentators have extended these concepts to governments, acting as fiduciaries, and their populations. In practice, the courts are reticent to impose a fiduciary relationship at public law. However, two lines of authority support the existence of fiduciary principles that are unique to public law. The first draws on the Canadian experience with a sui generis form of fiduciary relationship between the Crown and indigenous peoples, and later commentary on the principles of the Treaty of Waitangi. The second is judicial recognition that the relationship between local authorities and ratepayers is a fiduciary relationship. Breach argues that it is necessary to define fiduciary concepts that are unique to public law. This will avoid the uncertainty resulting from a sui generis classification, or worse, the consequences of conflating public law with private law fiduciary relationships. In doing so, he reassesses how the duty of loyalty can be understood in a public law context.